A biological basis for depression in pancreatic cancer. Issue 8 (28th January 2014) - Botwinick, Isadora C.; Pursell, Lisa; Yu, Gary; Cooper, Tom; Mann, J. John; Chabot, John A.
Abstract Background Patients with pancreatic adenocarcinoma frequently present with depression the symptoms of which may precede cancer diagnosis, suggesting that the pathophysiology of depression in pancreatic adenocarcinoma may result from biological changes that are induced by the presence of the tumour itself. The present study was conducted to test a hypothesized relationship with the kynurenine pathway, which has been implicated in both depression and tumour‐induced immunosuppression. Methods 17 patients with pancreatic adenocarcinoma were recruited and completed mood questionnaires (Functional Assessment of Cancer Therapy ‐Pancreatic Cancer, Beck Depression Inventory and the Beck Anxiety Inventory) and blood testing for serum levels of tryptophan, kynurenine, kynurenic acid and quinolinic acid. Tumour burden was determined from pathology reports (tumour size and nodal involvement). Results Findings indicated a negative correlation between mood scores and the plasma kynurenic acid : tryptophan ratio in plasma, and a positive correlation between tumour burden and plasma kynurenine level. Conclusions This study suggests that pancreatic cancer may influence mood via the kynurenine pathway. The relationship of the kynurenine pathway with pancreatic tumour burden should be explored further in large multicentre studies because a better understanding of this physiology might have significant clinical benefit.